TRPV4-dependent induction of a novel mammalian cold-inducible protein SRSF5 as well as CIRP and RBM3 - Takanori Fujita (Nature Portfolio, 2017)
Abstract Cold-inducible RNA-binding protein (CIRP) and RNA-binding motif protein 3 (RBM3) are two evolutionarily conserved RNA-binding proteins that are structurally related to hnRNPs and upregulated in response to moderately low temperatures in mammalian cells. Although contributions of splicing efficiency, the gene promoters activated upon mild hypothermia and the transcription factor Sp1 to induction of CIRP have been reported, precise mechanisms by which hypothermia and other stresses induce the expression of mammalian cold-inducible proteins (CIPs) are poorly understood. By screening the serine/arginine-rich splicing factors (SRSFs), we report that the transcript and protein levels of SRSF5 were increased in mammalian cells cultured at 32 °C. Expression of SRSF5 as well as CIRP and RBM3 were also induced by DNA damage, hypoxia, cycloheximide and hypotonicity. Immunohistochemical studies demonstrated that SRSF5 was constitutively expressed in male germ cells and the level was decreased in human testicular germ cell tumors. SRSF5 facilitated production of p19 H-RAS, and increased sensitivity to doxorubicin in human U-2 OS cells. Induction of CIPs was dependent on transient receptor potential vanilloid 4 (TRPV4) channel protein, but seemed independent of its ion channel activity. These findings indicate a previously unappreciated role for the TRP protein in linking environmental stress to splicing.